Longitudinal transmission pathways of borderline personality disorder symptoms: from mother to child? - Reinelt, Eva; Stopsack, Malte; Schumacher, Maren; Ulrich, Ines; Barnow, Sven (Psychopathology, 2014)
Background: There is evidence that the borderline symptomatology of the mother longitudinally predicts the number of borderline criteria met by the children. However, possible underlying mechanisms have rarely been examined. In line with transactional models of borderline personality disorder (BPD), we analyzed a broad concept of maladaptive mother-child interactions of mothers with BPD symptoms towards their children, including insensitive parenting and mother-child discrepancies, in reporting the child's psychopathological behavior. Sampling/Methods: The sample was drawn from the population-based Greifswald Family Study and consisted of 295 children and their biological mothers. Both were examined at two points in time, first when the children were about 15 years old (T₀) and again 5 years later (T1), using path analyses. Results: Maladaptive mother-child interactions (especially an overprotective and rejecting parenting style and high discrepancies regarding internalizing problems) mediate the longitudinal transmission of borderline symptoms from mother to child. Furthermore, our data revealed that this result is consistent for various youth symptoms which are associated with BPD such as impulsivity or dissociation. Conclusion: The data of the current study imply that the transmission of borderline symptoms from mother to child is mediated by maladaptive mother-child interactions. For this reason early and professional support may be useful to prevent these children from developing severe psychopathology.
Published online: May 22, 2013
Gesehen am 25.08.2014